The Effect of Intranasal Pressure on Intraocular Pressure - Esra Türkseven Kumral; Burak Erden; Nimet Yeşim Erçalık; Elvan Alper Şengü; Çetin Akpolat; Erdi Özdemir; Tolgar Lütfi Kumral; Ziya Saltürk (The Ophthalmology, 2017)
Purpose: The aim of this study was to evaluate intraocular pressure (IOP) after the application of the nasal packing for sinonasal surgery. Methods:A total of 40 patients who underwent sinonasal surgery were enrolled in this prospective study. Patients were randomly assigned into two groups: gauze packing (group 1) and silicone nasal septal splint (group 2). All participants completed a comprehensive questionnaire and underwent an ocular examination including measurement of IOP by Goldmann applanation tonometry (GAT). All the measurements were repeated before removing the nasal packings. IOP measurements before the operation and during the nasal packing were compared with each other. Results: The study group comprised 21 males (52.5 %) and 19 females (47.5%). The mean age was 29.10±8.18 years (median 27.50) (min-max=18-51). Twenty-three (57.5%) had silicone nasal packing while 17 (42.5%) had gauze nasal packing. Mean nasal packing duration was 2.575±0.712 days. The post-operative increase in the intraocular pressure of the both eyes were not statistically significant (p>0.05). IOPs of the patients’ eyes showed no significant increase, compared to the pre-operative results according to the type of nasal packing used (p>0.05). Conclusions: Increased intranasal pressure due to nasal packing did not increase intraocular pressure. The type of the nasal packing also did not differ to increase the intraocular pressure.